Vitamin K antagonists with or without long‐term antiplatelet therapy in outpatients with stable coronary artery disease and atrial fibrillation: Association with ischemic and bleeding events - Lemesle, Gilles (Clin Cardiol, 2017)
BACKGROUND: It remains uncertain whether patients with atrial fibrillation (AF) requiring long‐term oral anticoagulation (OAC) and with stable coronary artery disease (CAD) should receive antiplatelet therapy (APT) in addition to OAC. HYPOTHESIS: APT in addition to OAC would be more effective than OAC alone in preventing ischaemic events in such patients. METHODS: In the international REduction of Atherothrombosis for Continued Health (REACH) Registry including 68 236 outpatients with or at risk for atherothrombosis, we identified 2347 patients with stable CAD and AF receiving vitamin K antagonists (VKA). Using propensity score matching, patients treated with VKA (n = 1481) were compared with those receiving VKA + APT at inclusion (n = 866). The primary outcome was major adverse cardiovascular events (MACE) at 4 years (cardiovascular death, myocardial infarction, or stroke). Secondary outcomes were all‐cause death and bleeding leading to hospitalization and transfusion. RESULTS: Patients receiving VKA only were older (74 vs 72 years, P < 0.01), had less diabetes (37% vs 42%, P = 0.02), and less frequent history of percutaneous coronary intervention (28.7% vs 43.9%, P < 0.01). The mean CHA(2)DS(2)‐VaSc score was 4.9 in the VKA group vs 4.7 in the VKA + APT group (P < 0.01). After propensity score matching, the rate of MACE was similar between groups: hazard ratio = 1.01 (0.77‐1.33) (P = 0.94), whereas bleeding tended to be more frequent in the VKA + APT group: odds ratio = 1.87 (0.99‐3.50) (P = 0.051). CONCLUSIONS: In this observational analysis, the use of APT in addition to OAC in patients with stable CAD and AF was not associated with lower risk of ischemic events but possibly with higher bleeding rates. Randomized trials are necessary to determine the optimal long‐term antithrombotic strategy.